Alcohol Abuse and its impact on Aneurysmal Subarachnoid Hemorrhage: A Narrative Review of Risks, Mechanisms, and Clinical Outcomes - Mika, Wiktoria; Słowik, Justyna; Sieradzka, Izabela; Wajda, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction: Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating cerebrovascular event, and rigorous identification of modifiable risk factors is essential for effective prevention. Alcohol consumption is consistently cited as a potential risk factor, but the precise dose-response relationship and specific mechanisms linking alcohol to aneurysm rupture and prognosis remain controversial. This narrative review synthesizes available evidence to quantify the risk, elucidate underlying pathology, and determine the clinical implications of alcohol misuse in aSAH patients. Review of Available Knowledge: Epidemiological analysis demonstrates a statistically significant association only with heavy alcohol consumption, defined as consumption exceeding 30 grams per day. Compared to abstinence, heavy consumption increases the pooled relative risk (RR) of aSAH incidence to 1.78. A dose-response analysis confirmed a linear risk increase of 12.1% for every 10 grams/day increment. Pathophysiologically, acute alcohol ingestion impairs cerebral autoregulation, evidenced by an increased cerebrovascular resistance index (CVRi) during orthostatic stress, offering a plausible mechanism for acute rupture triggering. Clinically, pre-existing heavy drinking is an independent and powerful predictor of poor outcome one year post-hemorrhage, with an adjusted RR of 4.5 for dependence or death, reflecting compromised systemic and neurological reserves. Conclusions: Heavy alcohol consumption is a strong, quantifiable, modifiable risk factor for aSAH incidence and an independent determinant of poor functional prognosis. These findings mandate aggressive screening for Alcohol Use Disorder in individuals with unruptured intracranial aneurysms and necessitate tailored, proactive critical care management for heavy drinkers who suffer aSAH to mitigate heightened risks of secondary injury and dependency.